Catalytic Pyrolysis of Plastic Waste using Red Mud and Limestone: Pyrolytic Oil Production and Ignition characteristics - Ena Marlina; Akhmad Faruq Alhikami; Siti Asmaniyah Mardiyani; Trismawati Trismawati; Cepi Yazirin (Universitas Muhammadiyah Magelang, 2024)
This study investigated the catalytic pyrolysis of polypropylene (PP) and low-density polyethylene (LDPE) using 10 wt.% red mud and 10 wt.% limestone catalysts in a batch reactor. The process was conducted at an operating temperature of 350Â°C with retention times of 30, 60, and 90 minutes. The effects of adding red mud and limestone catalysts on the yields of liquid, solid, and gas pyrolysis products were analyzed. The pyrolytic oil was further evaluated using droplet evaporation measurements, equipped with a K-type thermocouple and a CCD camera to monitor droplet evolution within an atmospheric chamber. The addition of catalysts enhanced the liquid product yield while reducing the solid yield. The catalytic pyrolysis successfully facilitated the isomerization of plastic polymers, breaking the carbon chains of PP with 10 wt.% red mud. Olefin content increased by up to 7.3% for both 10 wt.% red mud and 10 wt.% limestone. Furthermore, the evaporation rate constant of the catalytic pyrolysis oils improved by up to 8.3%. This study aims to provide new insights into utilizing local waste materials to enhance the quality of pyrolytic plastic products.